Decreasing Physical Restraint in Acute Inpatient Psychiatric Hospitals: A Systematic Review. (September 2019) - Allen, Diane E.; Fetzer, Susan; Siefken, Caroline; Nadler-Moodie, Marlene; Goodman, Karen
OBJECTIVE: A systematic review was conducted to identify methods used to decrease the application of physical restraints in acute inpatient psychiatric hospitals.METHOD: A literature search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines using key words related to physical restraint.RESULTS: Three data-based studies met eligibility criteria.CONCLUSIONS: Findings suggest that multimodal intervention strategies may reduce the number of hours of physical restraint used in inpatient psychiatric settings, but quality evidence to support specific strategies is lacking. The search highlights the need for more quality research using standardized restraint reporting measures.